CÉSAR FRANCK’S GRANDE PIÈCE SIMPHONIQUE OP. 17 AN ANALYSIS FROM THE PERFORMER’S POINT OF VIEW - MIKLÓS, Noémi (Studia Universitatis Babes-Bolyai Musica, 2014)
As mentioned in the title, the following work contains the analysis of one of the most important works of César Franck and of the French organ literature, the Grande pièce symphonique op. 17. In order to realize a proper performance of this monumental work it is necessary to run through a series of structural, technical and performance issues which are essential in the process of understanding Franck’s organ music. The following analysis is structured in two main parts: the first part discusses the form of the work emphasising its main structural sections, whilst the second part handles the performance and the technical problems regarding articulation, dynamics, tempo and style.